God, Greed, and Governance: The Role of Islamic Symbolism in Concealing Corruption in Northeastern Kenya - Adan Saman Sheikh (ASTEEC, 2025)
This article explores how Islamic symbolism is used by political and business elites in Northeastern Kenya to obscure corrupt practices and maintain public legitimacy. Using a qualitative research design, the study draws on 40 semi-structured interviews, focus group discussions, and field observations across Garissa, Wajir, and Mandera counties. Five thematic findings emerge: the strategic use of religiosity for image control, institutional silence by religious leaders, community tolerance through moral trade-offs, ritualised governance performances, and widespread public cynicism coupled with resignation. While many participants recognised the disconnect between religious symbolism and ethical leadership, Islamic rituals and language continued to be effective in shielding elites from scrutiny. The study contributes to political sociology and Islamic studies debates by showing how religious identity when strategically performed, can serve as a moral shield that complicates accountability in fragile governance environments.